Tuberculosis infection among children under six in contact with smear positive cases: A study in a hyper endemic area of Iran. (February 2023) - Afshari, Mahdi; Dehmardeh, Atefeh; Hoseini, Aref; Moosazadeh, Mahmood
Abstract: Introduction: Annually, tens of millions of children are being exposed to tuberculosisinfection. Note that children are in higher risk of getting infection and sever types of the disease, detecting the factors associated with transmission of the tuberculosis infection and disease to the exposed children is necessary for disease prevention within the community. Methods: In this retrospective cohort study, 50 children under 6 who were in close contact with 25 smear-positive pulmonary tuberculosis cases in Sistan-Baloochistanprovine, Iran, were investigated. Demographic, behavioral and clinical characteristics of children and index cases were collected and tuberculosis infection and disease was assessed using the WHO guidelines. Results: Of 50 children exposed to the active cases, 12 (24 %) were infected to tuberculosis but none of them had active disease. We also found significant associations of the history of diabetes mellitus in the index cases (p = 0.043) and large family size (p = 0.026) with the increased risk of infection among the exposed children. Conclusion: Children under six which are in close contact with diabetic tuberculosis cases in large families are in higher risk of getting infection.